Are Relieving Maneuvers Useful in Diagnosis of Carpal Tunnel Syndrome? - Haydar Gok; Saime Ay; Sehim Kutlay (Archives of Rheumatology, 2008)
Objective: Our aim was to assess and compare the diagnostic accuracy of the carpal tunnel syndrome relief maneuver (CTS-RM) and the Flick sign for the diagnosis of carpal tunnel syndrome (CTS) in female patients. Materials and Methods: This is a diagnostic test study with blind comparison to a reference criterion. A total of 87 consecutive female patients with typical symptoms for CTS referred for electrophysiological examination were included in the study. Normal limits of nerve conduction were obtained from 50 healthy female subjects. After the electrodiagnostic assessment clinical evaluation was performed by a physician and it included testing of all patients for the CTS-RM and Flick sign. The diagnostic accuracy was evaluated for each test alone and in combination and sensitivity was correlated with the electrophysiological severity of CTS. Main outcome measures included the estimates of sensitivity, specificity, positive and negative likelihood ratios (PLR, NLR). Results: After electrophysiological assessment, 58 patients (pre-test probability, 67%) have been diagnosed as CTS. The sensitivity and specificity estimates were %81,86 for the CTS-RM and %69, 79 for the Flick maneuver. Combining a positive CTS-RM and Flick sign improved the specificity to 93%. The PLRs of the CTS-RM and Flick sign were 3.3 and 5.9 and the NLRs were 0.39 and 0.22 respectively. Combining a positive CTS-RM and Flick sign had the PLR of 9.5 and the NLR of 0.37. When evaluating the subjects with CTS, the CTS-RM detected significantly more subjects compared to the Flick sign. Conclusions: Our study reveals that the accuracy of Flick sign is low in the diagnosis of CTS. While the CTS-RM alone is helpful in confirming the diagnosis in patients with typical symptoms, combination with the Flick sign further improves its predictive accuracy. (Rheumatism 2008; 23: 129-34)